Seeing and Hearing the Thinking Voice - Gopinath, Gayatri (Current Musicology, 2018)
Given that my own work is focused on questions of diaspora, visuality, and queerness, I am very grateful for the fact that Fiol-Matta models for us a mode of both listening and looking with deep care. This critical listening and critical looking make apparent an entirely different understanding of Puerto Rican music culture, through an examination of how women singers have negotiated the impossible demands placed on their star bodies. Fiol-Matta theorizes for us the intimate relation between the visual and the aural. As such, her work in fact powerfully resonates with that of visual studies scholars such as Tina Campt, Christopher Pinney, and Krista Thompson. For instance, writing of the Afro–Puerto Rican icon Ruth Fernández, Fiol-Matta writes, “The photo as material object relies on the visual, while recordings obviously stress the aural. Yet both visual and aural belong to the sensorium of racism. These archival objects are interdependent; sound and gaze, visuality and aurality, work together in the perceiving subject’s sensorium. Fernandez’s first photos, today, compel us to the gaze, but we can’t obliterate the sound they were associated with” (75). Here Fiol-Matta’s reading of Fernandez’s photograph, in tandem with her recordings, practices the method that Tina Campt (2017) names “listening to images”: tuning in to their typically inaudible frequencies so as to open us up to their occluded meanings and interpretive possibilities. Fiol-Matta also writes of Fernández: “Under constant scrutiny, visually and vocally, she constructed a persona, literally a glittering surface to match the wonder her voice provoked” (72). We can understand this glittering, reflective surface of the female star body, as Fiol-Matta describes it, as an enactment of what Christopher Pinney (2003) names “surfacism,” or what Krista Thomson (2015) refers to as “shine”: strategies through which subaltern subjects embrace a kind of representational flatness, a refusal of depth, or a blinding hypervisibility, so as to deflect a dominant gaze that seeks mastery over a knowable, intelligible racial and gendered subject. • These are just two instances of the way that Fiol-Matta’s book schools us in a mode of both critical listening and critical looking, and as such is very much in conversation with visual studies scholars. I think there’s just as much to be gleaned from this book about the visual text of the star body as there is about its aurality. Secondly, I want to highlight the question of methodology and Fiol-Matta’s engagement with the archive. As was the case with Fiol-Matta’s first book, A Queer Mother for the Nation (2002), this book is a deeply archival project. Here, as in her earlier work, Fiol-Matta perfects the art of the critical biography. She expertly weaves the archival excavation of the lives and artistic output of each of the four figures in the book with a critical theorization of voice and gender, but she does this so seamlessly that we may fail initially to apprehend just how difficult this archival labor must have been. The work of critical biography is about grappling with what Fiol-Matta elsewhere calls the “permanent open-endedness of the archive” (2014, 49), as well as with its violent erasures and blanknesses. In restoring these artists to audibility by foregrounding their “thinking voice”—their subterfuge, sonic strategies—Fiol-Matta’s book is a resounding blow against what she terms the “shocking oblivion” (18) that characterizes the non-presence of these artists in the historical record not only as serious singers, but also as composers, producers, bandleaders, and the myriad other roles they played. Fiol-Matta demands that we remember these artists differently, outside the typically misogynist and homophobic interpretive frames through which they emerge in the historical record. In a particularly striking turn of phrase, Fiol-Matta writes of Myrta Silva: “Instead of remembering Silva as a bombshell who lost her sex appeal, we should remember her sonic licentiousness, the way she was the first Latino star to transform the culturally inflicted passive position of the woman into a putative bottom power” (28). Fiol-Matta’s reading of Silva as a quintessential power bottom recalls Hoang Nguyen’s explication of bottomhood not simply as a sexual position but also as an ethical model of relationality, a social alliance that extends to all those who inhabit various forms of racial, gender, and sexual abjection: the loca, the butch, the working-class woman, the jibara, the racial other. Fiol-Matta’s book maps out the ways in which all these abjected positions are in fact inhabited and transformed by these women into sites of bottom power, a place from which to critique the normative class, gender, racial, and sexual ideologies that bear down on them in the multiple national spaces they traverse (from PR and the US mainland, to Cuba, to Argentina, among other sites). This gets me to the final point I want to highlight in Fiol-Matta’s book: her central and suggestive theorization of nada, the nothingness. Throughout the book, Fiol-Matta variously refers to the nothing, along with the gap, the pause, the suspension, the nonplace, and the state of oblivion. As I understand it, Fiol-Matta reads the claim “to be nothing” on the part of an artist such as Lucecita Benítez as a queer strategy of fully inhabiting the place of lack, of oblivion, to which one is consigned within a misogynist and homophobic logic, as a way of refusing legibility within those terms. It is about demanding a pause, a silence, a moment of stillness, a suspension, of the dominant terms through which she is seen and heard. We can read the nothing not as a space of simple erasure or eradication, but rather, as Fiol-Matta puts it, as one of “productive density” (134), a “clearing to reconstruct the event of voice in multiple displacements” (171). Thus we can understand the nothing, as Fiol-Matta theorizes it, as a particularly queer mode of refusal that enables the thinking voice to come to the fore. While this is obviously a book about voice and gendered embodiment, and restoring to the historical record a way of truly hearing the thinking voice of these four artists, what I think emerges most strongly in these pages is Fiol-Matta’s own thinking voice: resonant, rigorous, lyrical, demanding, and always uncompromisingly queer. References Campt, Tina. 2017. Listening to Images. Durham, NC: Duke University Press. Fiol-Matta, Licia. 2002. Queer Mother for the Nation: The State and Gabriela Mistral. Minneapolis: University of Minnesota Press. ———. 2014. “A Queer Mother for the Nation Redux: Gabriela Mistral in the Twenty-First Century.” Radical History Review 120 (Fall): 35–51. Nguyen, Tan Hoang. 2014. A View from the Bottom: Asian American Masculinity and Sexual Representation. Durham, NC: Duke University Press. Pinney, Christopher. 2003. “Notes from the Surface of the Image.” In Photography’s Other Histories, edited by Christopher Pinney, 202–20. Durham, NC: Duke University Press. Thompson, Krista. 2015. Shine: The Visual Economy of Light in African Diasporic Practice. Durham, NC: Duke University Press.